Catecholaminergic polymorphic ventricular tachycardia detected by an implantable loop recorder in a child - Yakup Ergül; Neslihan Kiplapinar; Celal Akdeniz; Volkan Tuzcu (KARE Publishing, 2013)
We present a six-year-old boy with a history of recurrent syncope whose physical examination and family history were inconclusive. Laboratory findings, 12-lead ECG, chest radiography, Holter monitoring, event recorder monitoring, echocardiography, coronary computed tomography (CT) angiography, Brugada challenge test (ajmaline), cranial magnetic resonance imaging, and awake/sleep electroencephalogram were all unremarkable. Since syncope was exercise-induced, an electrophysiology study was also performed, but revealed no inducible ventricular arrhythmias. Implantable loop recorder (ILR) was implanted. Three weeks later, bidirectional ventricular tachycardia was found in ILR record during presyncope that was related to exercise. The patient, with the diagnosis of catecholaminergic polymorphic ventricular tachycardia, was started on highdose beta-blocker therapy. Due to the recurrence of syncopes despite the presence of beta-blockers, an implantable cardioverter defibrillator was implanted.